(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To evaluate the effects of surgical movement direction (advancement vs. setback) and magnitude on inferior alveolar nerve (IAN) recovery following bilateral sagittal split osteotomy (BSSO) over 24 months. Methods: A prospective cohort study enrolled 94 patients undergoing BSSO (47 advancements, 47 setbacks). IAN function was assessed at seven timepoints using the Visual Analog Scale (VAS) for subjective evaluation and the Zuniga classification for objective evaluation: Level A (two-point discrimination), Level B (static light touch), and Level C (pain/thermal thresholds). Statistical analyses included repeated-measures ANOVA (RM-ANOVA), Cochran’s Q, and multivariate logistic regression. Results: Neurosensory disturbance (NSD) peaked at one week (93.62% advancement; 95.74% setback). Level C fibers fully recovered by 12 months; Level A deficits persisted in 6.38% and 8.51% of patients at 24 months. Movement direction did not significantly affect NSD recovery (p > 0.05). Multivariate regression identified movement magnitude ≥5 mm (OR = 3.45; p = 0.01) and age ≥25 years (OR = 2.80; p = 0.03) as independent risk factors for persistent NSD at 6 months. VAS scores correlated strongly with Level A deficits (ρ = 0.79–0.90). Conclusion: IAN recovery after BSSO is independent of movement direction but significantly delayed by older age and larger surgical movements. Level A sensory assessment (two-point discrimination) most accurately reflects patient-reported long-term paresthesia.